PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF ARTICULATE STORYLINE PADA MATERI PENGINDERAAN JAUH - Ridhwan Ridhwan; Rima Meilita Sari (Jurnal Samudra Geografi, 2022)
This research and development aim to develop learning media in the form of an articulate storyline on remote sensing material. The development of learning media uses the development procedure of Borg and Gall which has been modified according to the research objectives. The development stages are carried out to produce prototypes that are ready to be tested to improve critical thinking skills. The stages of development are preliminary studies, planning, development of learning media prototypes, validation of material and media experts, prototype revisions, and field trials to test the product's practicality. The practicality test involves class XI students who have taken remote sensing material. The results of the media and material expert validation show that the product is feasible to use. The results of field trials show the feasibility of the product by 89.65%. The conclusion from this development is that the articulate storyline learning media is suitable and feasible to be used in the learning process in high school.